Myoclonic status epilepticus as a presentation of caspr2 antibody‐associated autoimmune encephalitis. Issue 4 (December 2014) - Ramanathan, Sudarshini; Wong, Chong H; Rahman, Zebunnessa; Dale, Russell C; Fulcher, David; Bleasel, Andrew F
<x xml:space="preserve">Abstract</x> We present a case of autoimmune encephalitis associated with antibodies targeting contactin‐associated protein‐like 2. This case is notable because of the presentation with myoclonic status epilepticus and the prolonged clinical course of refractory seizures, which are demonstrated in the accompanying videos, and not previously associated with this condition. Treatment with prednisone, intravenous immunoglobulin, plasma exchange, rituximab, cyclophosphamide, and mycophenolate mofetil resulted in significant functional improvement. Historically, myoclonic status epilepticus is associated with a grave prognosis and minimal chance of meaningful recovery. This case demonstrates that autoimmune encephalitis remains an important differential diagnosis in patients with such a presentation, and that early recognition and the appropriate institution of immunotherapy can result in seizure control and functional recovery. [Published with video sequences]